PONTIANAK CHRISTIAN PAGUYUBAN EFFORTS IN MAINTAINING MECHANICAL SOCIAL SOLIDARITY OF MEMBERS - Trinugroho, Agustinus Catur (Jurnal Pendidikan Sosiologi dan Humaniora, 2019)
The objective of this research was to know the effort of Paguyuban Kristen Jawi Pontianak maintain collective consciousness, religious ties and social ties. The research used descriptive method and qualitative approach. The techniques of data collection were observation, interview and the study of documentation. The research instruments were the directive of observation, directive of interview, and the documentation tools. This research showed that collective consciousness of the gemeinschaft is already. There is effort done maintain the collective consciousness as for mutually coordinate and worship priority.  This religious tie of the gemeinschaft is good enough. There is effort done maintain the religious tie is get the religous vacation on specific moments that run every year. Social tie of the gemeinschaft was good. There is effort done maintain the social tie as run with instilling tolerance to gemeinschaft members and set the schedule activity and then run that as consistance.